Gangguan Fungsi Hati pada Coronavirus Disease 2019 - Salsabila, Tasha; Waleleng, Bradley J.; Pandelaki, Karel (Universitas Sam Ratulangi, 2021)
Abstract: The incidence and death rate of COVID-19 in North Sulawesi Province continues to increase and data regarding abnormal liver function in COVID-19 is not yet available. This study was aimed to obtain the liver function in COVID-19 patients. This was a literature review study using two databases, namely Pubmed and ClinicalKey. Keywords used were abnormal liver function AND COVID-19, elevated alanine aminotransferase AND COVID-19, elevated aspartate aminotransferase AND COVID-19, elevated gamma-glutamyl transferase AND COVID-19, elevated alkaline phosphatase AND COVID-19, elevated total bilirubin AND COVID-19. After being selected, 10 literatures were obtained based on inclusion and exclusion criteria. The results showed that increased liver function often occurred in cases of COVID-19, but the increase did not reach twice of the normal value. The most frequent increases were in GGT, followed by ALT and AST, total bilirubin, and the least was the increase in ALP. All literatures reported that increased liver function was more common in males, and in severe COVID-19 patients reported by eight literatures. Five literatures reported that elevated liver function increased mortality in COVID-19 cases. In conclusion, there are increases in ALT, AST, ALP, GGT, and total bilirubin levels in COVID-19 patients.Keywords: abnormal liver function, COVID-19Â Abstrak: Angka kejadian dan angka kematian COVID-19 di Provinsi Sulawesi Utara terus bertambah sedangkan data mengenai gambaran gangguan fungsi hati pada COVID-19 belum tersedia. Penelitian ini bertujuan untuk mengetahui gambaran fungsi hati pada COVID-19. Jenis penelitian ialah literature review dengan pencarian data menggunakan dua database yaitu Pubmed dan ClinicalKey. Kata kunci yang digunakan yaitu abnormal liver function AND COVID-19, elevated alanine aminotransferase AND COVID-19, elevated aspartate aminotransferase AND COVID-19, elevated gamma-glutamyl transferase AND COVID-19, elevated alkaline phosphatase AND COVID-19, elevated total bilirubin AND COVID-19. Setelah diseleksi, didapatkan 10 literatur berdasarkan kriteria inklusi dan eksklusi. Penelitian ini mendapatkan bahwa peningkatan fungsi hati sering terjadi pada kasus COVID-19 namun peningkatannya tidak mencapai dua kali nilai normal. Peningkatan paling sering terjadi pada GGT, diikuti oleh ALT dan AST, bilirubin total, dan paling sedikit yaitu pada peningkatan ALP. Seluruh literatur melaporkan peningkatan fungsi hati lebih sering terjadi pada laki-laki dan pada kasus COVID-19 gejala berat dilaporkan oleh delapan literatur. Lima literatur melaporkan peningkatan fungsi hati meningkatkan mortalitas pada kasus COVID-19. Simpulan penelitian ini ialah, terdapat peningkatan kadar ALT, AST, ALP, GGT, dan bilirubin total pada penderita COVID-19.Kata kunci: gangguan fungsi Hati, COVID-19